Effect of repeated harvesting on the content of caffeic acid and seven species of caffeoylquinic acids in sweet potato leaves. Issue 8 (3rd August 2015) - Sasaki, Kazunori; Oki, Tomoyuki; Kai, Yumi; Nishiba, Yoichi; Okuno, Shigenori
Abstract: The purpose of this study was to investigate the effect of repeated harvesting on the content of caffeic acid (CA) and seven species of caffeoylquinic acids (CQAs) in sweet potato leaves using a newly developed high-performance liquid chromatography method. Six cultivars and two breeding lines were used in this study. Leaves were collected at monthly intervals from 1st harvest (May) to 4th harvest (August) in 2011 and 2012. ANOVA analysis revealed that the contents of CQAs were significantly different among all cultivars and breeding lines, but no significant differences were found for CA. No annual variation was confirmed in CA and CQAs. Repeated harvest of sweet potato leaves affected the content of only 4-CQA and 5-CQA. Post-hoc comparisons using Tukey's method indicated that the contents of 4-CQA and 5-CQA in sweet potato leaves harvested at first time were significantly higher compared to those at the other harvest times. Graphical abstract: : Contents of the article titled "Effect of repeated harvesting on the content of caffeic acid and seven species of caffeoylquinic acids in sweet potato leaves"